PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIANPRODUK HEALTHY BEVERAGE YEAH! DAN SINA DI KOTA SEMARANG - Muhammad Aziz Wicaksono; Hari Susanta Nugraha (Jurnal Ilmu Administrasi Bisnis, 2018)
This study is motivated by the needs of consumers of healthy beverage products are increasing. Healthy beverage products are foods and drinks without any containning harmful ingredients, which is not contain preservatives and also be free of substances that trigger cancer. In addition, these foods and drinks containning less sugar. There are several factors that cause the sales of healthy beverage products are inconsistent, there are price and promotion. The purpose of this study is to determine influencing consumers to make purchasing decisions healthy beverage products by the price and promotion factor. The type of this study is explanatory research. The technique of sampling is including nonprobability sampling that is purposive sampling. The sample in this study is 100 respondents who are consumers of healthy beverage products in Semarang City. Measurement of scale is using Likert scale. In this analysis used factor analysis with the help of SPSS 20.Based on the results of the analysis, price and promotion variables have an influence on purchasing decision of healthy beverage product. Price variable has the biggest influence that is 47,6%. Promotion variable has an effect of 35.5%. The conclusion of this research shows that price and promotion can influence consumer in making decision of purchasing healthy beverage product. Based on these results manufacturers healthy beverage, such as Yeah! and Sina should set the price of healthy beverage products in accordance with the benefits given, the price is not too high to be consumed every day, advertising messages more clear and interesting, and the promotion should be done more intensively so it is easier to find consumers.